Carabin Deficiency Aggravates Hepatic Ischemia-Reperfusion Injury Through Promoting Neutrophil Trafficking via Ras and Calcineurin Signaling - Ni, Xuhao; Wu, Xiao; Zhu, Xiao-Xu; Li, Jian-Hui; Yin, Xiao-Yu; Lu, Ling (Frontiers in Immunology, 2022)
Neutrophil infiltration plays an important role in the initial phase of hepatic ischemia and reperfusion injury (HIRI). Despite many different key molecules that have been reported to meditate neutrophil trafficking in HIRI, the mechanism of this process has not been fully elucidated. In this study, we found that Carabin deficiency in myeloid cells (LysMCre:Carabinfl/fl) aggravated IRI-induced hepatic injury and apoptosis through increasing the infiltration of CD11b+Ly6G+ neutrophils. ImmGen Datasets further revealed that Carabin was expressed in bone marrow neutrophils (GM.BM) but was significantly downregulated in thio-induced peripheral neutrophils (GN.Thio.PC), which was consistently verified by comparing GM.BM and liver-infiltrating neutrophils induced by IRI. Mechanistically, up-regulation of Carabin in GM.BM in vitro reduced the expression levels of P-selectin, E-selectin, and αvβ3 integrin through inhibiting Ras-ERK and Calcineurin-NFAT signaling. Furthermore, blocking P-selectin, E-selectin, and αvβ3 integrin in LysMCre:Carabinfl/fl mice decreased the frequency and number of CD11b+Ly6G+ neutrophils and reversed hepatic ischemiareperfusion damage. In conclusion, our results provide a new understanding of Carabin, such that it is expressed and functions not only in adaptive immune cells (T and B cells) but also in innate immune cells (neutrophils), contributing to the migration of neutrophils. These findings provide novel and promising therapeutic targets for the prevention of HIRI during liver transplantation or hepatic surgery.